2019
DOI: 10.21203/rs.2.16845/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children with Autism spectrum disorder are associated with gut microbiota disorder

Abstract: Purpose The aim of this study was to evaluate the occurrence and clinical characteristics of autism spectrum disorder (ASD) associated to the stable state of the gut microbiota. Methods A total of 9 children with ASD and 6 healthy children used as control were selected and feces samples were collected from all of them. The 16S gene ribosomal RNA sequencing was used to analyze the difference in gut microbiota between healthy control children and ASD patients. Results The results of 16S sequencing based on opera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In autism, groups consisting primarily Ruminococcaceae and Porphyromonadaceae families were enriched in the autism cohort, and Veillonellaceae underenriched in the autism cohort. This is in agreement with a previous studies [ 47 ], which found Ruminococcaceae enriched in children with autism and gastrointestinal disturbances, and Veillonellaceae underenriched in children with autism [ 48 ]. Porphyromonadaceae has been linked to major depressive disorder, suggesting a role for it in the gut-brain axis [ 49 ].…”
Section: Resultssupporting
confidence: 94%
“…In autism, groups consisting primarily Ruminococcaceae and Porphyromonadaceae families were enriched in the autism cohort, and Veillonellaceae underenriched in the autism cohort. This is in agreement with a previous studies [ 47 ], which found Ruminococcaceae enriched in children with autism and gastrointestinal disturbances, and Veillonellaceae underenriched in children with autism [ 48 ]. Porphyromonadaceae has been linked to major depressive disorder, suggesting a role for it in the gut-brain axis [ 49 ].…”
Section: Resultssupporting
confidence: 94%
“…It is necessary to collect information about children's residential environment in follow‐up studies to explore the relationship between residential environment and gut microbiota. Cao et al and Sun et al reported reduced levels of Lachnospiraceae and Prevotellaceae (Cao et al, 2021; Sun et al, 2019). There is growing evidence demonstrating that inflammatory activity, caused by disordered gut microbiota, might underlie the microbiota‐gut‐brain axis (Liu, Li, Wu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the GM has been suggested to be involved in the pathogenesis of ASD due to the frequent occurrence of gastrointestinal (GI) dysfunctions in ASD patients [14][15][16][17][18][19][20]. A large number of papers have revealed that the GM is significantly altered in patients with ASD or animal models of ASD when compared with that in their controls [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Colonization with GM from ASD individuals is sufficient to induce hallmark autistic behaviors in mice [35].…”
Section: Introductionmentioning
confidence: 99%